Minority ethnic media: challenges for the future. Issue 1 (2nd January 2022) - Tsai, Hsin-yi Sandy
ABSTRACT: Minority ethnic media play a unique role in preserving the languages, shaping the identity, and improving communication and cohesion of the ethnic groups it represents. However, traditional ethnic media outlets such as television channels and printed media worldwide have been facing decreasing viewership, especially because of strong competition from Internet media. Obtaining the support of people in the targeted ethnic group is critical and challenging. This paper elucidates the obstacles—dwindling viewership, competition from new media, and debates on intragroup and intergroup (intercultural) communication—that minority ethnic television channels face in many societies. By using the Taiwanese minority ethnic channel Hakka TV as an example, this study examined audiences' viewing behaviors with respect to both the terrestrial channel and its online platform. A National Survey on Hakka Population and Languages (supported by the Taiwan Hakka Affairs Council) and in-depth interviews were used to explore the relationships between ethnicity, language, and communication in ethnic media. The results indicate what ethnic media outlets should prioritize to increasing viewership. Methods by which these outlets can reach out to other ethnic groups and enhance multiculturalism are discussed.